Prevalence of sudden arrhythmic death syndrome-related genetic mutations in an Asian cohort of whole genome sequence. Issue 8 (28th June 2020) - Huang, Pang-Shuo; Hsieh, Chia-Shan; Chang, Sheng‐Nan; Chen, Jien-Jiun; Chiu, Fu-Chun; Wu, Cho-Kai; Hwang, Juey‐Jen; Chuang, Eric Y; Tsai, Chia‐Ti
Abstract: Aims: Recently, the spectrum of background mutation in the genes implicated in sudden arrhythmic death syndrome (SADS), has been elucidated in the Caucasian populations. However, this information is largely unknown in the Asian populations. Methods and results: We assessed the background rare variants (minor allele frequency < 0.01) of major SADS genes in whole genome sequence data of 1514 healthy Taiwanese subjects from the Taiwan Biobank. We found up to 45% of healthy subjects have a rare variant in at least one of the major SADS genes. Around 3.44% of healthy subjects had multiple mutations in one or multiple genes. The background mutation rates in long QT syndrome, catecholaminergic polymorphic ventricular tachycardia, and arrhythmogenic right ventricular cardiomyopathy genes were similar, but those in Brugada syndrome (BrS) ( SCN5A ) and hypertrophic cardiomyopathy (HCM) genes ( MYBPC3, MYH7, and TNNT2 ) were higher, compared to those reported in the Caucasian populations. Furthermore, the rate of incidental pathogenic variant was highest in MYBPC3 gene. Finally, the number of variant was proportional to the exon length of the gene ( R 2 = 0.486, P = 0.0056) but not related to its functional or evolutionary importance (degree of evolutionary conservation) ( R 2 = 0.0008, P = 0.9218), suggesting that the mutation was random. The ratio of variant number over exon nucleotide length was highest in MYBPC3, MYH7, and TNNT2 genes. Conclusion: Unique features of background SADS gene mutation in the Asian populations include higher prevalence of incidental variant in HCM, BrS, and long QT 3 ( SCN5A ) genes. HCM genes have the highest variant number per exon length.